2012
DOI: 10.1038/hr.2012.58
|View full text |Cite
|
Sign up to set email alerts
|

Intravital microscopy reveals endothelial dysfunction in resistance arterioles in Angiotensin II-induced hypertension

Abstract: It is known that hypertension is associated with endothelial dysfunction and that Angiotensin II (Ang II) is a key player in the pathogenesis of hypertension. We aimed to elucidate whether endothelial dysfunction is a specific feature of Ang II-mediated hypertension or a common finding of hypertension, independently of underlying etiology. We studied endothelial-dependent vasorelaxation in precapillary resistance arterioles and in various large-caliber conductance arteries in wild-type mice with Ang II-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Parent and coworkers found that inhibiting NO synthesis selectively reduced acetylcholine-induced vasodilatation in cardiac resistance vessels of dogs, but failed to prevent similar responses in conductance coronary vessels (Parent et al, 1996). Recently, our group has shown, using the same mouse model as applied in the present study, that angiotensin-II-mediated hypertension (2 kidney/1 clip Goldblatt model) leads to endothelium-dependent vasodysfunction in precapillary resistance arterioles, while this effect could not be reproduced in rings of large caliber conductance vessels from the same animals ex vivo (Schaefer et al, 2012).…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Parent and coworkers found that inhibiting NO synthesis selectively reduced acetylcholine-induced vasodilatation in cardiac resistance vessels of dogs, but failed to prevent similar responses in conductance coronary vessels (Parent et al, 1996). Recently, our group has shown, using the same mouse model as applied in the present study, that angiotensin-II-mediated hypertension (2 kidney/1 clip Goldblatt model) leads to endothelium-dependent vasodysfunction in precapillary resistance arterioles, while this effect could not be reproduced in rings of large caliber conductance vessels from the same animals ex vivo (Schaefer et al, 2012).…”
Section: Discussionmentioning
confidence: 83%
“…All data in the figures are rendered as mean ± SD. In analogy to previous publications (Schaefer et al, 2005(Schaefer et al, , 2012, endothelium-dependent (i.e. acetylcholine-induced) vasorelaxation was calculated as percent of total endothelium-independent (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations